Solar energy technology a scenario building for future strategic perspectives - Cepe, Louie L.; Imbang, Glen A. (Quezon City University of the Philippines Diliman, Technology Management Center, 2011)
The study was conducted to develop plausible scenarios for the solar energy technology that were used to develop strategies for the technology's improvement. Specifically, it aimed to identify the technological needs for the development of the solar PV; develop and analyze plausible scenarios for strategic planning; and recommend strategies for the improvement of the solar PV technology. The expert opinion technique was used for the scenario building process where the ten (10) steps in scenario planning were followed. The insights presented in the developed scenarios were used as the framework to carry out the technology road mapping technique. Three (3) scenarios were developed in relation to the number of financial institutions' participation and the availability of better Renewable Energy (RE) alternatives. The scenarios are generally positive about the use of RE sources and showed the future of the technology in generating power for the rural areas in the Philippines. Results showed that the private sector, financing institutions and the government are the key actors in the realization of the presented scenarios. The issue on climate change can also be considered as a key driver in the success of solar PVs. With regard the vulnerabilities in each of the presented scenarios, the solar PV technology's dependency on financing and support from the government was seen to be crucial in the long-run. The actualization of the presented scenarios will entail costs and resources and would require strong commitment from the key stakeholders. The social aspect of the solar PV technology was also seen as an important area that needs to be looked at. Several suggestions for the realization of the developed scenarios were made in this study. In the first scenario, the solution identified was the increase in R&D activities for solar PV technologies. The strategies formulated for this scenario can enhance the R&D capabilities of the country on solar PV technologies. The solution identified for the second scenario was the development of renewable energy technology awareness and development programs. The suggested strategy for this scenario could result to a well informed and up to date RE technology community that will put the involved stakeholders in a better position to decide. In the third scenario, the solution identified was the continuous investment on renewable energy R&D activities. The strategies presented in this scenario can counter its vulnerabilities by preparing the key stakeholders for future energy security.
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: Solar energy; Solar engines